Investigation of aerosol spatial distributions downstream of a critical orifice at low pressure - Bae, GN; Kinney, PD; Liu, BYH; Pui, DYH (ELSEVIER SCIENCE INC, 1998)
The spatial distribution of aerosol particles downstream of a critical orifice has been experimentally investigated. The measurements were performed by filtering the aerosol and visualizing the filter deposits. Measurements were made for a range of flow rates, pressures, and particle sizes. The most significant observation was that the particle spatial distributions changed from uniform to nonuniform when the downstream pressure was lowered below about 10 torr. Similar observations were made using in-situ particle monitors. These results may have significance for understanding particulate contamination in vacuum-based semiconductor process equipment. (C) 1998 American Association for Aerosol Research.
Keywords: PARTICLES; CONTAMINATION; EQUIPMENT; NOZZLE; VACUUM